Carcass fabrication yields of beef steers supplemented zilpaterol hydrochloride and offered ad libitum or maintenance energy intake() - Schmitz, Angela N (J Anim Sci, 2018)
An experiment was conducted to evaluate the fabrication yields of carcasses from beef steers supplemented zilpaterol hydrochloride (ZH) and fed at maintenance (MA) or ad libitum (AB) intake levels. Beef steers (n = 56) from a common sire were blocked (n = 28 per block) by terminal growth implant and sorted into pairs by BW. Four pairs (n = 8) were harvested on day 0; the remaining 24 pairs (n = 48) were assigned to a dietary intake level (MA or AB) and days on feed (28 or 56 d). Within pairs of MA or AB intakes, steers harvested on day 56 were randomly assigned to supplementation of ZH (90 mg·d(−1) per steer) for 20 d followed by a withdrawal period of 4 d or control (C). Steers (BW = 603.5 ± 48.1 kg) were harvested at a commercial processing facility. After a 24-h chill period, standard USDA grading procedures were used to derive a calculated yield grade and quality grade. Following grading, left carcass sides were transported to the West Texas A&M University Meat Laboratory for fabrication. Each side was fabricated into subprimals to determine individual red meat yield (RMY), trimmable fat yield (TFY), and bone yield (BY). A mixed model was used for analysis; fixed effects included treatment combinations and random effects included block and pairs. Single df contrasts tested day 0 vs. 28, day 0 vs. 56, day 28 vs. 56, MA vs. AB, and C vs. ZH. Yield of chuck eye roll differed (P = 0.05) by days on feed (0 d = 4.14, 28 d = 4.11, 56 d = 4.55%). Similarly, eye of round yield was impacted (P = 0.02) by days on feed (0 d = 1.51, 28 d = 1.37, 56 d = 1.36%). Additionally, brisket yield was altered (P < 0.01) by days on feed (0 d = 4.08, 28 d = 3.56, 56 d = 3.48%) and treatment (C = 3.34, ZH = 3.61%). For remaining subprimals, no differences (P ≥ 0.15) were detected. Furthermore, results indicated that RMY tended (P = 0.07) to differ by treatment (C = 61.35, ZH = 63.67%). Comparatively, TFY was impacted (P = 0.04) by intake (MA = 20.44, AB = 23.33%). Results from this study indicate that a MA intake level during the last 56 d of the finishing period concurrent with ZH supplementation impacts subprimal yields as well as carcass RMY and TFY of beef steers.